Розрахунок наведеного потенціалу в задачі високовольтного подільника напруги - Атарод, С.; Бржезицький, В.О.; Гаран, Я.О.; Маслюченко, І.М. (Електротехніка і електромеханіка, 2012)
A high-voltage voltage divider model allowing for effect of
induced potential of the high-voltage arm sections on the overall
electric field pattern is considered. A new computational method
for the divider high-voltage arm geometric parameters and its
separate sections induced potential is introduced, allowing to
refine its parameters of accuracy.